Development Mine Scheduling Concept in Making Pit Design - Dedi Yulhendra; Feraldo Sandrio; Adree Octova (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Planning a modern open pit mine requires a computer model of the resources and reserves to be mined, both block and grid models. With current technological developments and has entered almost all sectors including the mining sector, as for computer program packages (software) used by the mining industry, namely Microsoft excel, Mincom minescap and others. An evaluation and analysis system of mine plans/ mine schedules is necessary to make predictions of mining operations that will be carried out and can be used to find the cause of deviation or design deviations. There are several weaknesses in making scheduling manually, so scheduling is done using SPRY which is very helpful in the scheduling process.